EDUCATION AND POLITICS IN INDIA: STUDIES IN ORGANIZATION, SOCIETY AND POLICY (Editors: Susanne Hoeber Rudolph and Lloyd I. Rudolph) - Lipkin, John (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1973)
Susanne Hoeber Rudolph and Lloyd I. Rudolph, eds. EDUCATION AND POLITICS IN INDIA: STUDIES IN ORGANIZATION, SOCIETY AND POLICY. Cambridge: Harvard University Press, 1972. 470 pp. 20.00.